The connotations of the Black color in Arar's hair in his diwanah ashiyat Wadi Al-yabas - ظاهر محمد الزواهرة; حراحشة, أمينة; سليمان سالم الفرعين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of this Research was to Study the Connotations of the Black color in the hair of Arar in his Diwan "ashiyat Wadi Al-yabas" as a model and field of this Study, as the Black color and its synonyms are mentioned a lot in his Diwan, and the Research has Revealed the Following headings: the connotations of the Black color in the hair of Arar, color Synonyms of the Black color, the Relationship Between the Black color and the eyes.The Blackcolorhas Giventhe Poetictexta HighArtisticEnergy, fromthe usualSimpleConnotationstoMultiple and Valuable ColorConnotations, Revealingthe Psychological, Intellectual and Cultural Structuresofthe Poet, and Enriched the text Semantically and Artistically in the Contexts in which he was Employed. Keywords: Black color, Arar Mustafa Wahbi Al-Tal, ashiyat wad Al-yabas.